Evaluasi Program Pelatihan Moderasi Beragama Bagi Pemuda dengan Menggunakan Model Kirkpatrick di Balai Diklat Keagamaan Makassar - Milawati Milawati; Muhammad Nur Akbar Rasyid; Sitti Mania (Journal of Innovative and Creativity (Joecy), 2026)
The religious moderation strengthening training program for youth represents a strategic initiative by the Ministry of Religious Affairs to prevent radicalism and reinforce inter-religious tolerance. This evaluative research employs the Kirkpatrick model at 2 levels (levels 1 and 2) out of 4 levels to measure training effectiveness conducted by Makassar Religious Training Center (BDK) on November 18–20, 2025, with 30 youth participants from higher education institutions (UIN Alauddin, UIM, and UKI Paulus Makassar). Data were collected through satisfaction questionnaires (Level 1) and pre-post tests on tolerance knowledge (Level 2). Results indicate: Level 1 satisfaction reached 85.8% (materials, methods, facilitators, facilities, management); Level 2 knowledge improvement from pre-test score 78.93 to post-test 93.13 (gain 14.2 points, ±18%). Significant improvement supported by paired t-test (t=8.93; p<0.001), with 96% participants achieving competency ≥70. Findings confirm the program was well-designed and effectively transferred religious moderation understanding within a short three-day period, providing evidence-based insights for national program development.